IMPLEMENTING SEMAI: ENHANCING STUDENT LEADERSHIP THROUGH ROTATIONAL CLASS PRESIDENCY IN ELEMENTARY SCHOOLS - Burhanuddin Talib (Esteem Journal of English Education Study Programme, 2024)
The "Semua adalah pemimpin (SEMAI)" program at UPT SPF SDN Percontohan PAM Makassar tackles the problem of inequitable leadership chances among elementary students, which may impede the cultivation of essential social, emotional, and leadership competencies. The approach guarantees that each student acquires leadership experience by rotating the class presidency on a weekly basis. This qualitative, descriptive-exploratory study assesses the SEMAI program's impact, problems, and efficacy in promoting inclusive leadership, while examining its potential for wider implementation. The data gathering comprised comprehensive interviews, observations, and document analysis involving instructors, students, and parents. The findings indicated substantial enhancements in students' self-assurance, social engagement, and emotional control. Furthermore, the program diminished students' dependence on devices and motivated other initiatives at other educational institutions. Notwithstanding these achievements, issues including disparate levels of student engagement and heightened teacher effort were recognized. The study presents an innovative contribution to educational leadership by proposing a scalable, cost-effective methodology for fostering inclusivity and leadership abilities in primary education, a domain seldom investigated, especially in Indonesia. This strategy corresponds with international objectives for fair education and illustrates how these initiatives can mitigate systemic obstacles while promoting individual development and community influence.